Gastric microbiome-derived Lacticaseibacillus casei strain RIGLD MG-1 relieves Helicobacter pylori-induced inflammation in gastric epithelial cells in vitro - Ghasemipoor, Masoomeh; Yaghoubi-Avini, Mohammad; Azimirad, Masoumeh; Nabavi-Rad, Ali; Looha, Mehdi Azizmohammad; Doulberis, Michael; Schulz, Christian; Yadegar, Abbas (Molecular biology reports, 2025)
Background The burden of Helicobacter pylori infection is exacerbated by rising antibiotic resistance. Probiotics, especially Lactobacillus species, have shown potential as adjunctive therapies for H. pylori infection. This study aimed to isolate a Lactobacillus strain from the gastric microbiome of healthy individuals and assess its probiotic properties against H. pylori . Methods and results Gastric biopsies were obtained from a cohort of 10 subjects, and used for bacterial isolation. The Lactobacillus strain was identified to species level using PCR and sequencing, followed by safety assessments. MTT assay was employed to measure AGS cell viability after exposure to various concentrations of H. pylori , as well as live and pasteurized Lactobacillus . Anti-inflammatory properties of the probiotic strain were assessed in AGS cells using RT-qPCR and ELISA. Additionally, the strain’s potential to inhibit H. pylori adhesion and invasion was examined. Probiotic Lacticaseibacillus casei strain RIGLD MG-1 was isolated and characterized as non-pathogenic and found to be tolerant to acidic and bile-rich environments, and susceptible to several antibiotics. Live and pasteurized L. casei downregulated the expression of NF-κB , IL-8 , TNF-α , and β-catenin , meanwhile upregulated the expression of IL-10 in H. pylori -treated cells. They also alleviated H. pylori- induced proinflammatory response by lowering IL-8 and TNF-α, and boosting IL-10 production. Additionally, both probiotic forms inhibited H. pylori adhesion and invasion in AGS cells. Conclusion Our results show that L. casei strain RIGLD MG-1 is safe and demonstrates significant immunomodulatory and anti-adhesion effects, making it a potential probiotic for use as adjunctive therapy to mitigate H. pylori -induced inflammation.